GDL and MPL Characterization and Their Relevance to Fuel Cell Modelling. (14th September 2015) - Haußmann, Jan; Wilhelm, Florian; Enz, Simon; Klages, Merle; Pournemat, Anahid; Bergbreiter, Christian; Clark, Joseph Simon; Duraisamy, Keerthi; Seidenberger, Katrin; Markötter, Henning; Manke, Ingo; Scholta, Joachim
Abstract : Liquid water saturation of gas diffusion layer (GDL) pores limits gas transport leading to poor overall performance in polymer electrolyte membrane fuel cells (PEMFC). A survey of relevant parameters for GDL characterization, useful methods for investigations and the implications of these results to GDL modelling is provided. The GDL structure can be characterized using X-ray based methods. Structural information and surface parameters must be known to model the water distribution itself. Approaches for the determination of spatially resolved and integral surface property data are presented. For example, the inner contact angle can be determined by inverse gas chromatography. Other relevant parameters are the Leverett function, electrical and mechanical parameters such as E module and shear modulus G. Methods and results of the physical characterization are presented. The use of both structural and surface parameters is shown for Monte Carlo (MC) modelling describing the behavior of liquid water inside the porous fibre structure. Furthermore, these results are used to consider local changes in morphology and surface properties of the GDL and to improve full cell computational fluid dynamics (CFD) simulations of PEM fuel cells.